2004
DOI: 10.1093/nar/gkh745
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of tetraplex structures of the fragile X repeat sequence (CGG)n is mediated by homolog-conserved domains in three members of the hnRNP family

Abstract: Hairpin or tetrahelical structures formed by a d(CGG)n sequence in the FMR1 gene are thought to promote expansion of the repeat tract. Subsequent to this expansion FMR1 is silenced and fragile X syndrome ensues. The injurious effects of d(CGG)n secondary structures may potentially be countered by agents that act to decrease their stability. We showed previously that the hnRNP-related protein CBF-A destabilized G'2 bimolecular tetraplex structures of d(CGG)n. Analysis of mutant proteins revealed that the CBF-A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 41 publications
0
68
0
Order By: Relevance
“…In a more recent NMR study, G/G mismatches were shown to exist in a dynamic equilibrium between the anti-and syn-conformations required to form two symmetric hydrogen bonds between the N1 and carbonyl oxygen atoms of two guanines (31). The CGG repeats were also reported to form G-quadruplexes in both RNA (11)(12)(13) and DNA (14,15). In the current study, we analyzed the structural features of CGG and other types of CNG repeats under identical conditions using biochemical and biophysical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent NMR study, G/G mismatches were shown to exist in a dynamic equilibrium between the anti-and syn-conformations required to form two symmetric hydrogen bonds between the N1 and carbonyl oxygen atoms of two guanines (31). The CGG repeats were also reported to form G-quadruplexes in both RNA (11)(12)(13) and DNA (14,15). In the current study, we analyzed the structural features of CGG and other types of CNG repeats under identical conditions using biochemical and biophysical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, methylation of RGG motifs in FMRP by PMRT1 might regulate the interaction of FMRP with polyribosomes and G-quadruplex-containing mRNAs (81). In addition, members of the hnRNP A family were reported to destabilize G-quadruplex structures by a so-far unknown mechanism (44,82). Apart from FMRP and hnRNP A, there are several proteins described that are able to interact and modify G-quadruplex structures in DNA and RNA substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Neither bona fide Hnrpab RNA-binding sites nor consensus sites have been identified; however, its preference for G-and/or U-rich RNA or DNA has been reported (Kumar et al 1987;Sarig et al 1997;Khateb et al 2004;Raju et al 2008). Hnrpab1 specifically associates with AU-rich stability elements (AREs) of some mRNAs, suggesting a role in cell-type and differentiation-regulated mRNA stability for at least some mRNAs.…”
Section: The Nucleo-cytoplasmic Distribution Of Hnrpab Isoforms Suggementioning
confidence: 99%